The Importance of Teaching Science and Technology in Early Education Levels in an Emerging Economy. (June 2014) - Oliveros Ruiz, Maria Amparo; Vargas Osuna, Lidia; Valdez Salas, Benjamín; Schorr Wienner, Michael; Sevilla Garcia, Juan; Cabrera Cordova, Eduardo; Nedev, Roumen; Ibarra, Roberto
In the context of technological dissemination sessions aimed at prospective students at the Polytechnic University of Baja California in the city of Mexicali, Baja California, the importance of engineering and its role in scientific and technological progress was stressed, as well as its role in scientific and technological progress as drivers of economic development in the region. A group of 2, 154 students from 20 different institutions of public high school education answered a survey designed as an evaluation tool for a career path or technology area of interest. The survey results show that students have a low preference for engineering careers. Moreover, these results were augmented with an additional study on the high attrition of students in engineering schools in the city of Mexicali, Baja California, also conducted by the authors. It raises the importance of teaching science in the early education levels, which aims to prepare scientists and technologists needed for the development of research and innovation as a foundation for economic prosperity and welfare of an emerging economy such as Mexico.